2017
DOI: 10.1155/2017/6871081
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nitric Oxide on Renal Proximal Tubular Na+Transport

Abstract: Nitric oxide (NO) has a wide variety of physiological functions in the kidney. Besides the regulatory effects in intrarenal haemodynamics and glomerular microcirculation, in vivo studies reported the diuretic and natriuretic effects of NO. However, opposite results showing the stimulatory effect of NO on Na+ reabsorption in the proximal tubule led to an intense debate on its physiological roles. Animal studies have showed the biphasic effect of angiotensin II (Ang II) and the overall inhibitory effect of NO on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 93 publications
0
10
0
Order By: Relevance
“…; and (3) Can the vascular and/or tubular architecture influence the observations? All NOS isoforms are expressed in the kidney,38 and the synthesized NO itself is known to inhibit reabsorption of Na + along the nephron by reducing the respiratory rate of mitochondria8, 39, 40, 41 therefore, NO inhibits oxygen consumption. Three lines of evidence support our observations.…”
Section: Discussionmentioning
confidence: 99%
“…; and (3) Can the vascular and/or tubular architecture influence the observations? All NOS isoforms are expressed in the kidney,38 and the synthesized NO itself is known to inhibit reabsorption of Na + along the nephron by reducing the respiratory rate of mitochondria8, 39, 40, 41 therefore, NO inhibits oxygen consumption. Three lines of evidence support our observations.…”
Section: Discussionmentioning
confidence: 99%
“…First, hypertension and kidney disease have been associated with increased expression/activity of sodium transporters and enhanced sodium reabsorption [8,15]. NO has an inhibitory effect on the activity of several sodium transporters [79]. Thus, it is speculated that NO deficiency may fail to counterbalance the impaired sodium transporters induced by early-life insults, thus leading to programmed hypertension.…”
Section: Mechanisms Of Renal Programming Related To Nitric Oxide (mentioning
confidence: 99%
“…In addition to the physicochemical characterisation of the Nps-AEA/PCL obtained, we carried out in vitro biological activity tests as the quantification of iNOS expression in human proximal tubular epithelial cells. It is known that this inducible isoform of NOS is widely expressed in cells of the renal proximal tubule [42]. To highlight, several studies have reported on a promising antihypertensive effect (primarily vasodilator) of AEA mediated by NO release in different cell types [43][44][45].…”
Section: Discussionmentioning
confidence: 99%